STUDENTS’ ABILITY AT INFINITIVE AND GERUND CONSTRUCTION IN MASTERY IN WRITING DESCRIPTIVE TEXT BY USING PICTURE MEDIA AT MTs Al-JUMHURIYAH - Sindi Rasiska (XXXXXXXX, 2022)
The objective of this study was to know the effectiveness of using pictures media on students writng of descriptive text at seventh grade students of MTs Al-Jumhuriyah Deli Serdang. The method used in this study was quantitative research. The design of this study was quasiexperimental design to know the effectiveness of using picture media on students’ writing descriptive text. The result could be seen that using picture as media is effective and appropriate on students’ writing descriptive text. It could be seen from the average of post-test result in experimental class was 61,44 and the average of gained score was 16,48. The result of calculation showed that in the significance degree of 2.877 > 2.021. it means that t observation was higher than t table. According to the criteria of the test, it could be concluded that there wa a progress in using picture on students’ writing descriptive text. In conclusion, using picture on students’ writing descriptive text at sebenth grade students of MTs Al-Jumhuriyah Deli Serdang was effective.Keywords: Infinitive and Gerund, writing, descriptive text, and picture media